Numerical characterization of a piezoelectric composite with hollow metal fillers including new figures of merit, pore shape effects, and distinct piezoceramic types - Nasedkin, Andrey; Nassar, Mohamed Elsayed (International journal of mechanics and materials in design, 2022)
This paper focuses on the numerical analysis of the properties of porous piezoelectric composites with metal-doped pore surfaces and assesses their effectiveness as piezoelectric sensors and actuators. Two types of porous piezoelectric composite systems are considered: the ordinary porous system and the system with metalized pore surfaces (SMPS). The pore surfaces of the SMPS were anticipated to be entirely coated by a very thin metal layer. To determine the effective moduli, homogenization problems were solved numerically using the finite element analysis of the representative cells using the ANSYS APDL package. The homogenization problems were solved considering piezoceramics substrates with different anisotropy of piezomoduli and representative cells with cubic and spherical pores. Several figures of merit, including novel figures of merit intended towards actuator applications, have been researched to evaluate the performance of the SMPS. The results of computational experiments demonstrated that pore shape has less impact on the effective elastic and dielectric characteristics but has a greater effect on the values of the piezomoduli. For various piezoceramic materials in the composite matrix, effective piezomoduli are also subject to the greatest influence, particularly transverse and shear piezomoduli. Abnormal behavior of the transverse piezomodulus and an increase in dielectric permittivities were observed as the porosity fraction was enhanced. The transverse actuation effect of the SMPS rises dramatically with increasing porosity. In this regard, it was concluded that piezoelectric transducers built from the SMPS may be efficiently employed in various actuators based on the transverse piezoelectric effect and transverse vibration modes.